Role of Tumor-Derived Chemokines in Osteolytic Bone Metastasis - Coniglio, Salvatore J. (Frontiers in Endocrinology, 2018)
Metastasis is the primary cause of mortality and morbidity in cancer patients. The bone marrow is a common destination for many malignant cancers including breast carcinoma, prostate carcinoma, multiple myeloma, lung carcinoma, uterine cancer, thyroid cancer, bladder cancer and neuroblastoma. The molecular mechanism by which metastatic cancer are able to recognize, infiltrate and colonize bone are still unclear. Chemokines are small soluble proteins which under normal physiological conditions mediate chemotactic trafficking of leukocytes to specific tissues in the body. In the context of metastasis, the best characterized role for the chemokine system is in the regulation of primary tumor growth, survival, invasion and homing to specific secondary sites. However, there is ample evidence that metastatic tumors exploit chemokines to modulate the metastatic niche within bone which ultimately results in osteolytic bone disease. In this review, we examine the role of chemokines in metastatic tumor growth within bone. In particular, the chemokines CCL2, CCL3, IL-8/CXCL8 and CXCL12 are consistently involved in promoting osteoclastogenesis and tumor growth. We will also evaluate the suitability of chemokines as targets for chemotherapy with the use of neutralizing antibodies and chemokine receptor specific antagonists.